2022
DOI: 10.3390/su142315982
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal Carbonization vs. Pyrolysis: Effect on the Porosity of the Activated Carbon Materials

Abstract: Porous carbon materials (specific area over 2400 m2 g−1) were obtained from birch wood chips, the waste of its thermochemical processing water-insoluble lignocellulosic pyrolysis tar, and their mixture, by thermochemical activation with NaOH at 800 °C. Raw materials were carbonized by two methods: pyrolysis (500 °C) and hydrothermal (250 °C) treatment. The elemental and chemical composition of precursors and the effect of these parameters on the obtained carbon materials’ structure and porosity were studied. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…Authors of studies regarding the activation process with potassium and sodium hydroxides usually point to a similar interaction mechanism with organic raw materials [40,41]. However, the bulk of published work is devoted to KOH studies, although, in comparison with NaOH, this hydroxide has higher molecular weight, higher melting point and higher price and is, therefore, less economically feasible, while being more environment friendly, since it potentially can be used as fertilizer in agriculture.…”
Section: Characteristics Of Chemical Composition and Structure Of Car...mentioning
confidence: 99%
“…Authors of studies regarding the activation process with potassium and sodium hydroxides usually point to a similar interaction mechanism with organic raw materials [40,41]. However, the bulk of published work is devoted to KOH studies, although, in comparison with NaOH, this hydroxide has higher molecular weight, higher melting point and higher price and is, therefore, less economically feasible, while being more environment friendly, since it potentially can be used as fertilizer in agriculture.…”
Section: Characteristics Of Chemical Composition and Structure Of Car...mentioning
confidence: 99%
“…The raw material, birch wood, was first pre-treated using hydrothermal carbonization, which was performed in a PARR-4554 (USA) autoclave at 260 • C for 4 h [75]. Then, 20 g of the resulting carbonizate was mixed with 60 g of NaOH and heated at 700 • C in an inert gas atmosphere to obtain activated carbon based on birch wood after hydrothermal carbonization (AHTC).…”
Section: Synthesis Of Carbon Materialsmentioning
confidence: 99%
“…Activated carbons (activator, NaOH, to precursor ratio 3:1, temperature 800 • C) from wood (samples APYR-W and A-HTC-W), lignocellulose pyrolysis tar (samples APYR-T and A-HTC-T) and their mixture (1:1) (samples APYR-H and A-HTC-H) were obtained after thermal (500 • C-PYR) and hydrothermal treatment (250 • C-HTC) carbonization (synthesis and material properties described elsewhere [5]). These precursors were mixed with dicyandiamide (DCDA) solution in DMF (ratio of DCDA: precursor was 20:1).…”
Section: Nitrogen Dopingmentioning
confidence: 99%
“…The presence of carbohydrate and aromatic polymers in the biomass, as well as the use of residues of chemical processing of wood with a predominance of one or the other component, makes it possible to obtain carbon materials with different structures [3,4]. For example, it has been found that the alkaline activation of pyrolysis wood tar, which is formed after the extraction of sugars from bio-oil (levoglucosan production technology) and has high lignin content, can be used as an individual precursor or as part of a composite with wood to obtain micro-mesoporous activated carbon [5]. In the production of activated carbons preliminary carbonized precursors are usually used for processing, with thermal carbonization (or pyrolysis) being a traditional approach.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation